Three novel MOFs constructed from 1, 3, 5-tris(1-imidazolyl)benzene and dicarboxylate ligands with selective adsorption for C2H2/C2H4 and C2H6/CH4. Issue 12 (8th March 2022) - Yang, Ming-Xing; Chen, Li-Juan; Gao, Jing; Gao, Yang; Yu, Guang-Tao; Lin, Shen
Abstract : Three 3D porous Co-MOFs constructed from 1, 3, 5-tris(1-imidazolyl)benzene and dicarboxylic acid ligands with selective adsorption for unsaturated hydrocarbon molecules (C2 H2, C2 H4 ) and saturated hydrocarbon molecules (C2 H6, CH4 ). Abstract : The urothermal reactions of Co(ii )/Zn(ii ) salts with the diverse carboxylic acid and 1, 3, 5, -tris(1-imidazolyl)benzene(tib) ligands afforded three novel MOFs, namely, [Co3 (tib)2 (abdc)2 (ox)]2 ·6H2 O (1 ), [Co3 O(tib)(abdc)2 (DMI)]·2DMI·2H2 O (2 ) and [Zn3 I2 (tib)2 (napdc)2 ]·2DMI·2H2 O (3 ), (H2 abdc = 5-amino-1, 3-benzenedicarboxylate, H2 napdc = 1, 4-naphthalene dicarboxylic acid and DMI = 1, 3-dimethyl-2-imidazolidinone). In compounds 1 and 2, the Co(ii ) atoms are connected by polycarboxylate ligands to form two-dimensional (2D) layers that are pillared by tib ligands leading to the formation of 3D porous frameworks. In compound 3, the Zn(ii ) atoms are linked by tib ligands to form one-dimensional ribbon-like chains which are further connected by polycarboxylate ligands, making a 3D framework possible. Compound 1 can selectively adsorb unsaturated hydrocarbon molecules (C2 H2 and C2 H4 ) and saturated hydrocarbon molecules (C2 H6 and CH4 ). Specifically, compound 1 has high IAST selectivity for acetylene and methane (0.50 : 0.50, v/v) at 273 K and 1 bar. DFT calculations reveal that the π-conjugated hexagonal carbon ring may be the primary adsorption site because there are π–π interactions between the unsaturated hydrocarbon molecules (C2 H2 and C2 H4 ) and the π-conjugated hexagonal carbon ring in the framework of compound 1 .